HUBUNGAN PENERAPAN REINFORCEMENT DAN PUNISHMENT DENGAN MOTIVASI BELAJAR SISWA SMA KELAS XI DI KOTA BANDUNG - Syifa Rizqi Amalia, - (2021)
This study titled "The Relationship between the Implementation of Reinforcement and Punishment with the Learning Motivation of Class XI Senior High School Students in Bandung City" have a purpose to describe the significance of the relationship between the application of reinforcement and student learning motivation, to describe the significance of the relationship between the application of reinforcement and student learning motivation and to determine the significance of the relationship between the application of reinforcement and student learning motivation together. The reason for carrying out this research was because the researcher wanted to examine whether there is a significant relationship between the application of reinforcement and punishment with student learning motivation. The solution of this research is to find the alternatives to substitute punishment for student. This study used a quantitative approach with descriptive research methods using correlational research patterns. Data collection techniques in this research used questionnaires and interviews. The sample in this study were all class XI high school students who came from SMA Negeri 25 Bandung City and SMA Lab school UPI Bandung City and using the cluser random sampling technique. The result of this study was that there was a significant relationship between reinforcement and student learning motivation which was indicated by the results of the significance test (2-tailed) of this reinforcement variable of 0.030 <0.05. Which means that, between the reinforcement variable and the learning motivation variable, there was a significant relationship. Whereas in the significance test (2-tailed) punishment variable, the results can be obtained 0.992> 0.05. Which means that, between the punishment variable and the learning motivation variable, there was no significant relationship. And for multiple correlation test the probability value (sig. F change) shows the number 0.068. Because the sig. F change 0.068> 0.05, then the decision is Hₒ rejected and Hₗ accepted. That means, there was a significant relationship between the application of reinforcement and punishment with student learning motivation. The conclusion of this study is there was a relationship between reinforcement and student learning motivation, there was no relationship between the punishment and the learning motivation, and there was a relationship between the application of reinforcement and punishment with student learning motivation collectively Key words: reinforcement, punishment, learning motivation, quantitative approach, correlation research.